Exploring How Mentor Incentive Mechanisms in the Context of Resource Allocation Promote Sustainable Quality Enhancement in Residency Training: An Educational Phenomenology Study - Wang, Hui (Journal of Qualitative Research in Education, 2025)
This qualitative study explores how mentor incentive mechanisms shape educational experiences and learning outcomes within residency training programs, adopting an interpretive paradigm to understand participants' lived experiences. Through in-depth interviews with 42 participants—24 clinical mentors and 18 residents—across provincial and municipal tertiary hospitals in nine provinces spanning eastern, central, and western China, we employed thematic analysis to uncover rich narratives about teaching practices and educational resource dynamics from dual perspectives.Five key themes emerged. First, incentive structures were dominated by material rewards, while recognition of teaching excellence and pedagogical development opportunities remained undervalued, with notable disparities favoring eastern regions. Second, educational resource accessibility emerged as a crucial bridge connecting incentive experiences to teaching effectiveness, suggesting mentors' motivation translates into quality instruction primarily through enhanced resource utilization rather than direct pathways. Third, different incentive forms fostered distinct educational processes: compensation stability enabled sustained mentor-learner relationships, professional development opportunities enriched teaching methodologies, while collegial recognition cultivated collaborative learning environments. Fourth, training outcomes revealed multidimensional learning trajectories, with technical competencies developing strongly while higher-order clinical reasoning and professional identity formation required deeper mentorship attention. Fifth, enhancing residency education demands constructing layered recognition systems responsive to diverse mentor needs, strengthening pedagogical resource infrastructure, and establishing continuous dialogue mechanisms between educators and learners. These findings illuminate how institutional recognition practices shape teaching commitment and learner development in professional education settings.